PERANAN SUNAN AMPEL DALAM DAKWAH ISLAM DAN PEMBENTUKAN MASYARAKAT MUSLIM NUSANTARA DI AMPELDENTA - Hamiyatun, Nur (Dakwah, 2019)
Islam entered the archipelago through several figures called Walisongo. Sheikh Maulana Malik Ibrahim was a leader and pioneer in the field of da'wah who succeeded in forming students to carry out his missions in preaching to the Archipelago and that had happened since the 15th century AD The Walisongo figures I studied were; Sunan Ampel who first came only briefly or stopped by the land of Java with the intention of looking at his aunt until finally settled in Java. Then, the way of preaching carried out by Sunan Ampel by means of da'wah without any element of coercion or the path of peace.                                                                                                                                                                                                                       Sunan Ampel conducts the spread of Islam in Majapahit with permission from Prabu Brawijaya, so that Sunan Ampel has full rights for Islamization in the Majapahit area. Furthermore, Sunan Ampel established a boarding school in the main door area of ??the Majapahit kingdom where the Islamic boarding school area is a gift from Prabu Brawijaya. In the preaching carried out by Sunan Ampel, he has several tactics in the spread of Islam that I mentioned above. Then the students who were guided by Sunan Ampel also participated in the spread of Islam in all directions. Keywords : Sunan Ampel, Da'wah and Muslim Ampeldenta